Daya Hambat Ekstrak Daun Tembakau terhadap Pertumbuhan Mikroba Rongga Mulut - Riria Hendarto Putri; Izzata Barid; Banun Kusumawardani (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2014)
Oral cavity diseases can be caused by the oral microbes  such as Streptococcus mutans, Porphyromonas gingivalis and Candida albicans. The oral microbes growth can be inhibited by chlorhexidine gluconate mouthwash, but its long term use have adverse effects, therefore it is important to do a further research to find effective antibacterial and antifungal as alternative substance mouthwash. Flavonoid compounds in tobacco leaf have potential as an antibacterial and antifungal. The objective was to analyze the inhibition effect of tobacco leaf extract to the growth of Streptococcus mutans, Porphyromonas Gingivalis and Candida albicans. This research used 20%, 40%, 60%, 80% and 100% ethanol extract of tobaco leaf,  1% DMSO as negative control and 0.2% chlorhexidine gluconate as positive control. Antibacterial and antifungal activities were tested by diffusion disc method with four repetitions. The observation was conducted by measuring the diameter of inhibition zone after incubating for 24 and 48 hours. The largest inhibition zone of Streptococcus mutans growth were producted by ethanol extract of tobacco leaf with 80% concentration, the largest inhibition zone on Porphyromonas gingivalis and Candida albicans growth were produced by ethanol extract of tobaco leaf with 100% concentration. Diameter of inhibition zone ethanol extract of tobacco leaf was equal with the diameter of inhibition zone of 0.2 % chlorhexidine gluconate. The conclusion described that ethanol extract of tobacco leaf can inhibit the growth of Streptococcus mutans, Porphyromonas gingivalis and Candida albicans.